Bean technology adoption and its impact on smallholder farmers’ productivity, bean consumption; and food security data, Zimbabwe - Katungi, Enid Mbabazi; Makotore, Walter; Mutua, Mercy Muli; Mutari, Bruce; Kalemera, Sylvia Monica; Maereka Enoch (2025)
This data was derived from the 2018 nationwide endline survey of a project that evaluated the adoption and impact of improved bean varieties in Zimbabwe. The country, a PABRA member, was a flagship for a 2014 initiative aimed at enhancing food security and incomes through bean research. The endline survey was implemented as an activity of the flagship initiative funded by Swiss Agency for Development and Cooperation (SDC) and Global Affairs Canada (formerly Canadian International Development Agency [CIDA]) through the Pan-Africa Bean Research Alliance (PABRA)/CIAT and the Southern Africa Bean Research Network (SABRN). The dataset was analyzed to determine the degree of influence project interventions had on bean production, the utilization of promoted technologies, and overall household welfare. Furthermore, the collection aimed to derive lessons on the efficacy and underlying reasons for the outcomes of various interventions.